PENGELOLAAN PERPUSTAKAAN SEKOLAH - Irwandi; Resdianto Permata Raharjo (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The purpose of this study is to describe the strategy for managing the library at Ahmad Wahid Hasyim Middle School, Jombang. This research is a qualitative research. As a source of information in this research is the library manager. Data collection uses observation techniques, structured interviews and documentation. The results showed that the management of the library in this school had managed the school's library facilities well. To find out who is on board at the library, the school principal establishes an organizational structure for managing the library as the executor of daily activities. The head of the library management conducts an evaluation with the aim of finding out what is lacking in an effort to develop the library which will be used as input for improving the organization of the library in the following academic year.